RECONSTRUCTION OF QUR'AN-BASED ISLAMIC RELIGIOUS EDUCATION LEARNING: DIMENSIONS AND PRINCIPLES FOR THE CONTEMPORARY ERA - Nur Alfiyah; Esa Nur Wahyuni; Mohammad Asrori; Putri Ayu Dwi Nabila (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Improving the quality of Islamic Religious Education (PAI) learning is becoming increasingly important amid the challenges of globalization and digitalization, especially when spiritual values often receive less attention in modern education. This article aims to examine the concept of Islamic Education learning in the Qur'anic perspective, focusing on the dimensions and principles of learning that are relevant for the contemporary era. This research uses a literature study approach with content analysis of Qur'anic verses related to education, as well as literature review of academic journals and book literature. Data were collected through literature review and analyzed descriptively-qualitatively to identify a comprehensive conceptual framework. The results showed that the Qur'an offers a holistic educational framework that includes cognitive, affective, and psychomotor dimensions, as well as principles such as exemplarity, relevance, justice, patience, and development of individual potential. The integration of Qur'anic values into innovative learning strategies, such as project-based methods and the utilization of digital media has the potential to create relevant, effective, and meaningful learning experiences for learners.